4-Methoxylonchocarpin protects against cisplatin induced acute kidney injury via regulating ferroptosis - Nan Jiao; Baodong Wang; Qiong Zhang; Yuxiang Liu; Fen Zhao (Renal Failure)
Background Traditional Chinese medicine active ingredients have been increasingly recognized for their pivotal role in the treatment of acute kidney injury (AKI).Methods This study aimed to investigate the reno-protective effects and underlying mechanisms of 4-Methoxylonchocarpin (4ML), an extract from Abrus precatorius Linne, in a cisplatin-induced AKI model. Kidney injury was assessed through a comprehensive evaluation of renal function indicators and histopathological changes. The impact of 4ML on ferroptosis and AMPK pathways was examined by measuring lipid peroxidation biomarkers and iron ion following low and high dose 4ML treatments in mice. In vitro experiments, using HK-2 cells to assess ferroptosis biomarkers and cell proliferation with or without 4ML treatment, and in the presence of selective inhibitors or activators of ferroptosis and AMPK, to elucidate the potential mechanisms.Results 4ML administration significantly attenuated cisplatin-induced AKI in both mice models and HK-2 cells. Mechanistic studies revealed that 4ML treatment markedly reduced ferroptosis and activated the AMPK pathway, as evidenced by altered expression levels of GSH, GPX4, MDA, LPO, and iron ions. The activation of AMPK pathway by 4ML contributed to the amelioration of AKI. Conversely, the induction of ferroptosis and inhibition of AMPK attenuated the protective effects of 4ML.Conclusion These findings suggest that 4ML as a promising therapeutic agent for cisplatin-induced AKI, primarily through inhibiting ferroptosis and regulating AMPK. This study provides further evidence supporting the potential of traditional Chinese medicine-derived compounds in the management of AKI.